Analyzing and modeling urban sprawl and land use changes in a developing city using a CA-Markovian approach - M. Tajbakhsh; H. Memarian; Y. Shahrokhi (Global Journal of Environmental Science and Management)
Mashhad City, according to the latest official statistics of the country is the second populated city after Tehran and is the biggest metropolis in the east of Iran. Considering the rapid growth of the population over the last three decades, the city’s development area has been extended, significantly. This significant expansion has impacted natural lands on suburb and even some parts e.g. rangelands and agricultural area have been transited to urban land uses. The study was aimed at analyzing and simulating land use changes in Mashhad, Iran. The work needs a model to simulate land use changes among multiple categories and combine spatial and temporal changes during the projection period. Thus, Cellular Automata-Markov model was chosen to meet this target. In this work, the projected time period corresponded to the final 20-year vision period of all-round development of Iran for the target point of  2025 based on a long-term plan. Multi criteria evaluation approach integrated along with analytic hierarchy process were employed for preparing suitability maps for the five land uses, i.e. urban continuous patches, urban discontinuous patches, rural patches, agricultural lands, and range lands. Having applied the matrices utilized in model calibration, the best kappa coefficient proved to be associated with the land use maps dated 1996 and 2002. The Kappa index of quantity and allocation agreement was determined to be 0.9189 and 0.9529, respectively, which established an almost perfect agreement between simulated and observed land uses according to the year 2015. Change detection results showed that with the physical expansion of urban continuous patches, range lands and agricultural lands mostly transited to urban discontinuous patches and eventually were promoted to urban continuous texture. These developments or gains in urbanized patches will lead to some loses in agricultural lands and rangelands of the suburb in 2025. In addition, the analysis of projected land use map indicated that over the upcoming years, the development of the city in northern front, especially in northwestern region will be more intense with a higher speed in comparison with the other regions.